2009
DOI: 10.1080/03008200802714925
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Laminin Isoforms, Receptors, and Binding Proteins Unique to Nucleus Pulposus Cells of Immature Intervertebral Disc

Abstract: Intervertebral disc (IVD) disorders are believed to be related to aging-related cell loss and phenotypic changes, as well as biochemical and structural changes in the extracellular matrix of the nucleus pulposus (NP) region. Previously, we found that the laminin γ1 chain was more highly expressed in immature NP porcine tissues, in parallel with the expression pattern for a laminin receptor, integrin α6 subunit, as compared to adjacent anulus fibrosus region; suggesting that cell-matrix interactions may be uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
75
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 71 publications
(60 reference statements)
12
75
0
Order By: Relevance
“…In the young, healthy human, the NP ECM elasticity ranges from 0.3-5 kPa [56,57] and is comprised primarily of water (70-90% of wet weight), proteoglycans (65% of dry weight), and randomly oriented type II collagen (15-20% dry weight) [58][59][60]. Other compositionally minor (though potentially critical functionally) ECM components of the NP include elastin, small proteoglycans, and minor coUagens (types III, VI, IX) [61][62][63], and laminins [25,64,65]. Many of these ECM constituents can directly interact with NP cells through cell-surface receptors, if resident within the cell pericellular matrix or multicell cluster (e.g., type VI collagen, N-cadherin [53]); altemately, these ECM constituents can exert a mechanical influence upon NP cells through regulating nutrient transport, hydration (e.g., fixed charge density) and swelling pressure [66].…”
Section: Np Cells and Their Native Ecm Microenvironmentmentioning
confidence: 99%
“…In the young, healthy human, the NP ECM elasticity ranges from 0.3-5 kPa [56,57] and is comprised primarily of water (70-90% of wet weight), proteoglycans (65% of dry weight), and randomly oriented type II collagen (15-20% dry weight) [58][59][60]. Other compositionally minor (though potentially critical functionally) ECM components of the NP include elastin, small proteoglycans, and minor coUagens (types III, VI, IX) [61][62][63], and laminins [25,64,65]. Many of these ECM constituents can directly interact with NP cells through cell-surface receptors, if resident within the cell pericellular matrix or multicell cluster (e.g., type VI collagen, N-cadherin [53]); altemately, these ECM constituents can exert a mechanical influence upon NP cells through regulating nutrient transport, hydration (e.g., fixed charge density) and swelling pressure [66].…”
Section: Np Cells and Their Native Ecm Microenvironmentmentioning
confidence: 99%
“…This, in turn, will allow a more thorough understanding, at the molecular level, of the fate and role of notochordal or notochord-derived cells in the IVD and provide further insight into ways to tackle disc degeneration. Lamins are heterodimeric proteins involved in cell adhesion, migration, proliferation, differentiation and survival [74,77] Pending questions and potential clinical implications…”
Section: Cd239mentioning
confidence: 99%
“…Integrins and CD239 are expressed by NP cells and are responsible for their adhesion to laminins [74,77] Integrin subunits a3, a6 and ß4)…”
Section: Porcinementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, at least 15 isoforms of laminin have been identified; these are expressed differently in various tissues [83,84]. In NPCs, a higher expression of the laminin a5 chain, laminin receptor integrin subunits a3, a6, and b4 along with CD239 and CD151 were found compared to cells from the AF [85]. Gilchrist et al also examined the cell-matrix interactions and found a faster cell spreading and a higher resistance to detachment on laminin isoforms LM-511 and LM-332, in contrast to LM-111, fibronectin, and collagen II [86].…”
Section: Integrin-mediated Interactions Between Npcs and Ecmmentioning
confidence: 97%